Hydrological characters of coal reservoir and their significances on coalbed methane development: A review - Xinyue ZHAO; Bo WEI; Liang YUAN; Yanyan GE; Yong HU; Xin LI; Maomao WANG; Chao JIA; SHAN Mayila·AI; Jijun TIAN (Meitan kexue jishu, 2023)
The development of coalbed methane resources in China has broad prospects, and the evolution process of coalbed water and its transportation law has important impacts on coalbed methane production capacity. This paper clarifies the composition, properties, sources and isotopic chronology of coal reservoir water, analyzes the expansion law of the pressure drop funnel and the inter-well interference mechanism during the water transport process, discusses the reservoir damage that may be caused by the water transport during drainage, and puts forward several suggestions for coalbed methane development according to the evolution of coal reservoir water and its transport and migration law during production. The results show that: (1) coal reservoir water is originated from primary sedimentary water, infiltration water, deep-forming water and diagenetic water, and the sodium-chlorine coefficient (rNa+/rCl−), Scholler coefficient (IBE), and mineralization degree of the original sedimentary water is<0.5, >0.129, and >10000 mg/L, respectively; corresponding values of infiltration water are the opposite of these relations; the δD and δ18O of deep-forming water is ranged from −80‰ to+40‰ and +7‰ to +9.5 ‰, respectively; the δD and δ18O of diagenetic water is ranged from −65‰ to −20‰ and +5‰ to+25‰, respectively; (2) the geochemical characteristics of coal reservoir water have important indicative significances for the enrichment and development of coalbed methane, and the high gas-containing areas of coalbed methane usually have the characteristics of low sodium-chlorine coefficient, low desulfurization coefficient, low magnesium-calcium coefficient, and high degree of metamorphism, correspondingly, the low gas-containing areas have the opposite characters; (3) the pressure drop funnel propagation during coal reservoir water transport and migration and the interference between wells are conducive to improve the coalbed methane production, and most of the coalbed methane wells in China are deployed by rectangular or diamond-shaped well networks, and the optimal well space is usually ranged between 250m and 400m; (4) the water transport of coal reservoirs can cause pulverized coal to block the formation, water lock damage, water sensitive damage, and velocity sensitive damage. To reduce reservoir damage, implementing reasonable drainage strength, optimizing the well network, and adding waterproof locking agent and pulverized coal dispersant to the incoming fluid are suggested. The research results can provide a certain theoretical basis for improving the exploration efficiency and coalbed methane yield in China.